Synthesis and antimicrobial evaluation of novel 3-(arylideneamino)-3a, 8a-dihydroxy-1, 3, 3a, 8a-tetrahydroindeno[1, 2-d]imidazole-2, 8-diones and their 2-thioxo analogues. Issue 12 (18th June 2017) - Saini, Yeshwinder; Khajuria, Rajni; Kaur, Ramneet; Kaul, Sanjana; Sharma, Tanwi; Gupta, Suruchi; Gupta, Vivek K.; Kant, Rajni; Kapoor, Kamal K.
ABSTRACT: The preparation of some novel 3-(arylideneamino)-3a, 8a-dihydroxy-1, 3, 3a, 8a-tetrahydroindeno[1, 2- d ]imidazole-2, 8-diones8(i–xiv) and 3-(arylideneamino)-3a, 8a-dihydroxy-2-thioxo-1, 3, 3a, 8a-tetrahydroindeno[1, 2- d ]imidazol-8(2 H )-ones9(i–xiv) have been reported through one-pot catalyst-free reaction of aldehydes, semicarbazide hydrochloride/thiosemicarbazide with ninhydrin. All the synthesized compounds have been screened for antimicrobial activity and some of them were observed to possess broad spectrum antibacterial potential as well as significant antagonistic potential against fungal pathogens. GRAPHICAL ABSTRACT: